Formation of electrons’ and ions’ flows in the background plasma at the initial stage of the beam-plasma instability - Tanygina, D.M.; Anisimov, I.O.; Levitsky, S.M. (Вопросы атомной науки и техники, 2012)
Formation of the flow of the background plasma electrons moving to the electron beam injector at the initial stage of the beam-plasma instability development in the region of maximum HF electric field intensity is demonstrated via 1D computer simulation. Effect is caused by the plasma density profile deformation due to the pressure of the inhomogeneous HF electric field.